Pengukuran Beban Kerja Fisik dan Mental Pada Pekerja Menggunakan Metode Cardiovascular Load (CVL) dan NASA-TLX - Anwar, Arsya Amira; Yuamita, Ferida (Jurnal TRINISTIK: Jurnal Teknik Industri, Bisnis Digital, dan Teknik Logistik, 2024)
This study examines the effects of physical and psychological exhaustion on Balai P2P Jawa III employees, taking into account their age, gender, and way of life. The term "physical and mental workload" describes staff activities or tasks involving physical, mental, and/or physical strength. If a worker's workload surpasses their physical and mental capabilities, several adverse effects may arise, such as exhaustion and further health issues. In addition to developing efficient management techniques to lessen physical and mental exhaustion and enhance performance in the workplace, the goal of this research on workload measurement is to comprehend the influence on worker well-being and productivity. The objective of this study is to quantify physical workload using the Cardiovascular Load (CVL) method. Based on the average %CVL result of 12.67% and the similar %HR Revers data, it can be concluded that there is no physical weariness among the 10 workers. According to the NASA-TLX approach, four employees from three distinct divisions are facing a high level of mental workload, with a percentage ranging from 99.97% to 99.99%. The results of this study may be used to inform the creation of workplace fatigue management plans that are more individualised and suited to the needs of each division's personnel.